Characterization of medicine students regarding Research Methodology in Cienfuegos Medical School. - Dunia Reyes Hernández; Raúl López Fernández; Monica González Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Introduction: University excellence is linked to excellence in the educative process and research field. Objective: To determine the knowledge level about Research Methodology of Medicine students, including those in Mario Muñoz Monroy group. Methods: This study was developed in the Medicine School in Cienfuegos with a stratified sample using measurable instruments. Results: Students do not know the different kinds research, the variables and the most frequent statistic techniques.